Analisis Dan Perancangan Sistem Pelayanan Pengajuan Polis Online Pada PT Asuransi Jiwa Sequislife - Dewanto, I. Joko (Lembaga Penerbitan Universitas Esa Unggul, 2008)
System of service Insurance expendÃ‚Â by online this objective for help PT. Asuransi Jiwa Sequislife apply commit concurrent with member system of marketing service insurance. With any online service system to built present policy insurance even member loyality, to gimmick visitor for going to the member. Methodology to use development system with metode UML. With analysis and design this result perhapsÃ‚Â service system not standar service member the wisdom system for recommended have help maintenance data processing present policy, clain, policy active, policy change attract nasabah and general visitor,Ã‚Â The wisdom to minimum time use member for use present.Ã‚Â Keywords: Insurance, UML Diagram, Policy Present, Claim, Policy Active, Policy Change